Assessment of interfacial viscoelastic properties of Faba bean (Vicia faba) protein-adsorbed O/W layers as a function of pH. (May 2019) - Felix, Manuel; Romero, Alberto; Carrera-Sanchez, Cecilio; Guerrero, Antonio
Abstract: Interfacial rheology may be regarded as a powerful tool dominating the dynamics of complex fluid-fluid interfaces. More specifically, rheological properties from shear measurements have been postulated as the most useful technique for the assessment of the microstructure of complex fluid-fluid interfaces, and its relationship to long-term emulsion stability. The aim of this work was to evaluate the interfacial properties of Faba bean (FB) protein as a function of protein concentration and pH value (3.0, 5.0 and 8.0). The comparison between results obtained from dilatational and interfacial shear measurements provides accurate details related to the microstructure of the protein at the O/W interface. Viscoelastic moduli of the protein adsorbed at the O/W interface were obtained through dilatational measurements (Tracker, IT Concept), as well as interfacial SAOS measurements, using a double wall-ring geometry fitted to a DHR3 rheometer (TA Intruments). Results from dilatational rheology indicate that proteins are able to form a film at O/W interface, whose strength depends on the pH value (where E' ranges from 2.0·10 −2  Pa m at pH 5.0 to 5.5·10 −3  Pa m at pH 8.0). However, these measurements have shown to be less sensitive to pH modifications than interfacial shear viscoelastic measurements. Regardless of the pH value, interfacial shear measurements can follow the evolution of the viscoelastic behaviour of the O/W interfacial layer over the development of the protein gel network, as protein adsorption proceeds. This evolution indicates that protein adsorption takes place much faster at pH 3.0 and 5.0 than at pH 8.0. Graphical abstract: Image 100815 Highlights: The rheological behaviour of faba ben protein adsorbed is highly pH dependent. The formation of viscoelastic films can be followed by interfacial shear rheology. The best rheological behaviour and fastest protein adsorption take place at pH 3.0. Maxwel Generalized model can be used for protein-based interfacial layers.